Cystolepiota flavolamellata (Verrucosporaceae, Agaricales), a new species from Southeast Asia - Salichanh, Thaviphone; Sysouphanthong, Phongeun; Thongklang, Naritsada; Luangharn, Thatsanee (Phytotaxa, 2024)
We present Cystolepiota flavolamellata a new species discovered in the tropical regions of Thailand and Laos. Morphological characters and multigene phylogenetic analyses, which encompass ITS, LSU, rpb2, and tef1 sequences, distinguish this species. Cystolepiota flavolamellata exhibits the following unique set of characteristics: basidiomata covered with light brown to brown granules or large pyramidal squamules; free yellowish white to light yellow lamellae; broadly ellipsoid to oblong-amygdaliform to ovoid basidiospores; absence of pleurocystidia; variably shaped cheilocystidia, i.e., oblong, clavate with or without appendicular apex, conical to utriform, fusiform; an epithelium for the pileus and stipe covering; and presence of clamp connections. Molecular analyses based on multiple genes confirm its separation from other known and sequenced Cystolepiota species.